The Implementation Of Communicative Language Teaching (CLT) To Teach Spoken Recounts In Senior High School - Rusnawati, Eri (LPPM Universitas PGRI Adi Buana Surabaya, 2015)
The research objectives of the study are to describe the implementation of teaching and learning of spoken recounts and to investigate the students’ responses to the use of Communicative Language Teaching for spoken recounts. This research analyzes the gathered data qualitatively. This research describes the phenomenon that happens in the classroom. The data of this study were students’ behavior and responses in learning spoken recount by using CLT. The subjects were students of grade ten consisting of 34 students. Observation and interview were employed to collect data in teaching spoken recount through three activities (presentation, role-play, and doing procedure). The research findings show that CLT enhance Students’ speaking in learning recounts. Based on students’ achievement graph the students’ grammar, vocabulary, pronunciation, fluency and performance have significantly increased. It means students’ spoken recounts performance is increased. If presentation was placed in the end of activity steps, the students’ spoken recount performance would be even better. In conclusion, CLT implementation with its three practices contributes to students’ speaking in learning recounts and even CLT leads students to have courage in constructing meaningful communication confidently